Construction Automation with Bio-inspired Hierarchical Extremely Modular Systems - Zawidzka, Ela; Zawidzki, Machi (Journal of Automation, Mobile Robotics and Intelligent Systems, 2025)
This paper presents the concept of hierarchical extremely modular systems (EMS). The biology-inspired nomenclature, genetic encoding, and operations for this class of structures is introduced and illustrated with various examples. Four mutation types are introduced and briefly analyzed. A relatively good convergence of the evolution strategy-based algorithm applied for optimization of EMS is shown.